Finance for normal people how investors and markets behave - Statman, Meir (London Oxford University Press, 2019)
" Finance for Normal People teaches behavioral finance to people like you and me - normal people, neither rational nor irrational. We are consumers, savers, investors, and managers - corporate managers, money managers, financial advisers, and all other financial professionals. The book guides us to know our wants-including hope for riches, protection from poverty, caring for family, sincere social responsibility and high social status. It teaches financial facts and human behavior, including making cognitive and emotional shortcuts and avoiding cognitive and emotional errors such as overconfidence, hindsight, exaggerated fear, and unrealistic hope. And it guides us to banish ignorance, gain knowledge, and increase the ratio of smart to foolish behavior on our way to what we want. These lessons of behavioral finance draw on what we know about us-normal people-including our wants, cognition, and emotions. And they draw on the roles of these factors in saving and spending, portfolio construction, returns we can expect from our investments, and whether we can hope to beat the market. Meir Statman, a founder of behavioral finance, draws on his extensive research and the research of many others to build a unified structure of behavioral finance. Its foundation blocks include normal behavior, behavioral portfolio theory, behavioral life-cycle theory, behavioral asset pricing theory, and behavioral market efficiency. "--
"Behavioral finance is finance for normal people, like you and me. This book is also about transformation from normal-ignorant to normal-knowledgeable, learning the lessons of behavioral finance and applying them to banish ignorance, gain knowledge, and increase the ratio of smart to stupid behavior on our way to what we want. This book offers behavioral finance as a unified structure that incorporates parts of standard finance, replaces others, and includes bridges between theory, evidence, and practice"--
Machine generated contents note: -- Introduction: What is Behavioral Finance? -- Part 1: Behavioral People are Normal People -- Chapter 1: Normal People -- Chapter 2: Our Wants for Utilitarian, Expressive, and Emotional Benefits -- Chapter 3: Cognitive Shortcuts and Errors -- Chapter 4: Emotional Shortcuts and Errors -- Chapter 5: Correcting Cognitive and Emotional Errors -- Chapter 6: Experienced Happiness, Life-Evaluation, and Choices: Expected Utility Theory and Prospect Theory -- Chapter 7: Behavioral Finance Puzzles: The Dividend Puzzle, the Disposition Puzzle, and the Puzzles of Dollar-Cost-Averaging and Time-Diversification -- Part 2: Behavioral Finance in Portfolios, Life-Cycles, Asset Prices, and Market Efficiency -- Chapter 8: Behavioral Portfolios -- Chapter 9: Behavioral Life-Cycles of Saving and Spending -- Chapter 10: Behavioral Asset Pricing -- Chapter 11: Behavioral Market Efficiency -- Chapter 12: Lessons of Behavioral Finance.
Includes bibliographical references (pages 389-430) and indexes.
Keywords: Finance, Personal; BUSINESS & ECONOMICS / Budgeting; PSYCHOLOGY / Applied Psychology